Training of Development Video Based Learning in Optimizing the Merdeka Teaching Platform in Elementary Schools - Fery Muhamad Firdaus; Tika Aprilia; Amalia Rizki Ardiansyah (STKIP Singkawang, 2022)
This regional development has been carried out in the field of education, where education plays a role in developing the potential and competence of human resources who can develop their area through critical, creative thinking, and innovative works for the progress of the region. Elementary schools in Mlati district, Sleman Regency are the potential area to be advanced because of the access and education network that is quite supportive. In contrast, there are many teachers who have not been able to use these facilities in their classrooms. Most elementary school teachers in Kapanewon Mlati have not optimized the independent teaching platform that has been provided by the government, they still use videos from Youtube as teaching materials. Meanwhile, creative teachers must have the ability to develop learning strategies and teaching materials independently. Therefore, the purpose of this community service program is to improve services in the field of education to the local community through training that assists teachers in the development of learning strategies and teaching materials in the application of independent learning according to the demands of the curriculum in elementary schools. The results of the training showed that participants' understanding of video-based learning and independent teaching platforms increased before and after conducted the training. In the cognitive aspect, the average score of participants before training (pretest) was 45 and after the training (posttest) increased to 89. Meanwhile, from the aspect of skills in making learning videos, 85% or 28 participants from a total of 30 training participants have been able to make learning videos with PPT, Zoom meetings, and Bandicam applications. In detail, the number of participants who make learning videos with applications in the form of PPT is 10 participants (30% of the number of participants), zoom meetings 10 participants (30% of the number of participants), and 8 participants for Bandicam (25% of the total participants).